O silenciamento pedagógico diante do rompimento da barragem de fundão: uma análise a partir da escola estadual “Padre José Epifânio Gonçalves” - Cilésia Maria de Oliveira Carvalho (2022)
This thesis presents a qualitative study on the consequences caused by the the Fundão dam burst, owned by Samarco mining company, on the Padre José Epifânio Gonçalves State School (EEPJEG), in Barra Longa, Minas Gerais. This is originally a rural school, now located in the urban area of the municipality. It serves mostly students belonging to the peasant population who has suffered damages of physical, social and pedagogical aspects. The main objective of this study was to identify how the Fundão dam burst triggered changes at the school. To achieve the objective, the investigation was guided by the following question: how did the Fundão dam burst provoke the school to deal with the mining issue? As for a theoretical basis, three axes that support the study discussion were used: Rural Education with emphasis on three principles, and Education and Mining and the Pedagogical Silence within the dam burst context. In the methodology, to collect data, a search of documents already existing in the school was carried out. The Minutes of Module II Meetings (MMMII), from 2015 to 2020, were the documents analyzed. The study of these documents are grounded on Content Analysis and Thematic Analysis. In the analysis, there was evidence of “silencing” toward the school pedagogical practice regarding the dam burst, education and mining. The results presented contribute to the discussion about the themes on education and mining, and about Rural Education in pedagogical practice during teachers’ continuing education - Module II Meetings.